Heavy Metal Pollution and Ecological Risk Assessment in Soils Adjacent to Electrical Generators in Ramadi City, Iraq - AL-Heety , Lina F.D.; Hasan, Omer M.; Al-Heety, Emad A. Mohammed Salih (Iraqi Journal of Science, 2021)
This study aims to evaluate the concentration of the heavy metals (Co, Cd, Cr, Cu, Ni, Pb, and Zn) and their ecological risk in soils adjacent to the power generators of Ramadi city, Iraq. The soil samples were collected from a depth of 20cm. The obtained results showed that the mean concentrations of heavy metals (HMs) are ranked as in the following order: Cr (360.90mg/kg) > Ni (283.65mg/kg) > Zn (190.96mg/kg) > Pb (130.75 mg/kg) > Cu (36.54 mg/kg) > Co (16.62 mg/kg) > Cd (2.55 mg/kg). The mean values of HMs concentration exceed the international guidelines. The result of correlation matrix analysis at P £ 0.05 showed significant correlations between the concentrations of HMs. These correlations are interpreted in the context of a common source of pollution and/or common origin. Results of the potential ecological risk factor assessment of metal i (Eir) in soil adjacent to the power generators of Ramadi city showed that the Eir values take the following descending order: Ni (354.56, very severe) > Cd (255.31, severe) , Co (207.77, severe) > Zn (88.69, heavy) > Cu (25.73, light) > Cr (17.43, light) > Pb (12.0, light). The potential ecological risk index (RI) values are classified as severe ecological risk for all studied heavy metals. This study provides the environmental protection managers and decision-makers with important information about the risk of using electrical generators in residential neighborhoods.